1969
DOI: 10.1203/00006450-196905000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Ventilation of Newborn Infants I. The Effect of Rate and Pressure on Arterial Oxygenation of Infants with Respiratory Distress Syndrome

Abstract: ExtractThis study reports the effect of varying specific parameters of mechanical ventilation on aortic PO, in six infants with severe respiratory distress syndrome. Twenty-seven studies were performed during the first 168 hours of mechanical ventilation. I n each study, arterial oxygen partial pressure was found to vary directly with airway pressure a n d inversely with respiratory rate. No correlation was found between rate and pressure, or PaO,, PaCO,, a n d p H a . Oxygenation of infants with severe respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1973
1973
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…In the end, many infants died because they could not be weaned from mechanical ventilation. Early experience at the University of Pennsylvania by Jack Downes, (13) at the Hospital for Sick Children in Toronto by Paul Swyer,(14) and at Stanford University by Penelope Cave-Smith and colleagues (15) demonstrated that some mechanically ventilated neonates (especially those requiring short-term mechanical ventilation) survived. However, many of the survivors had severe chronic lung disease (16) that persisted into adulthood.…”
Section: Early Mechanical Ventilationmentioning
confidence: 97%
“…In the end, many infants died because they could not be weaned from mechanical ventilation. Early experience at the University of Pennsylvania by Jack Downes, (13) at the Hospital for Sick Children in Toronto by Paul Swyer,(14) and at Stanford University by Penelope Cave-Smith and colleagues (15) demonstrated that some mechanically ventilated neonates (especially those requiring short-term mechanical ventilation) survived. However, many of the survivors had severe chronic lung disease (16) that persisted into adulthood.…”
Section: Early Mechanical Ventilationmentioning
confidence: 97%
“…Mammel et al [13] also reported that the conventional mechanical ventilator was the superior form of ventila tory therapy, as compared to the high-fre quency jet ventilation which is thought to produce a more uniform gas distribution in the lung.…”
Section: Discussionmentioning
confidence: 99%
“…This rise in PaCC>2 returned to the control levels by decreasing ventilation to the initial rate of 37.5/min. This study demon strates that rapid-rate ventilation using a constant-flow and time-cycled ventilator is inferior to slow-rate ventilation in the diseased lung model.In the treatment of infants with hyaline membrane disease, many physicians generally use respirator settings with a slow rate, longer inspiratory time and large tidal volume, as Reynolds [11] and Smith et al [13] have rec ommended. However, some studies [2,7,9] suggest that a rapid-rate ventilation associated with a lower inspiratory pressure and a short inspiratory time improves arterial oxygena tion and also reduces barotrauma, especially air leaks or pulmonary interstitial emphysema associated with mechanical ventilation.…”
mentioning
confidence: 99%
“…Patrick Bouvier Kennedy, son of the president, was born at 34 weeks' gestation and died in a hyperbaric oxygen chamber in 1963, as mechanical ventilation was thought to be too extreme and experimental for this child. As the concept and practice of mechanical ventilation for newborns moved from a desperate, last-ditch therapy to something many were at least willing to consider, it was clear that almost nothing was understood about how to do it [4]. In retrospect, the relationship of delivered pressures, both peak and end-expiratory, to the delivery of tidal and minute volumes seems obvious.…”
Section: Introductionmentioning
confidence: 94%